Policy Evaluation Of The Pagar Dewa Village Head Of Ondok Kelapa District, Bengkulu Central District In The Use Of Village Funds In 2020 - Mirwansyah Mirwansyah; Asnawati Asnawati; Antonio Imanda; Bando Amin C. Kader (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to determine the "Policy Evaluation of Pagar Dewa Village Head, Pondok Kelapa Sub-District, Central Bengkulu Regency in the Use of Village Funds in 2020". Data collection techniques were carried out by means of in-depth interviews, observation and documentation. After the research results were obtained, they were analyzed by means of data reduction, data presentation and conclusion drawing. There were 5 informants in this study consisting of 2 key informants and 3 main informants. The theory used in this research is the theory According to Wayne Parsons (2008:549-552), there are two kinds of policy evaluation models used, namely Formative Evaluation and Summative Evaluation. Based on the results of the study, conclusions can be drawn, namely: 1. Formative Evaluation: a. The implementation of Village Government, the services provided by village officials are quite good but there needs to be improvements in providing services for the community. b. In the field of Village Development Implementation, the construction of concrete rebate roads is of poor quality, seen that the resilience of the building is still very lacking even though the village has budgeted a very large amount. c. The field of Community Development, training, meetings and competitions held by the village or outside the village, the village head always provides information on activities to the community. d. In the field of Community Empowerment, in planning and making programs in the village, everything is involved from the village head, village officials, community leaders, BPD leaders, traditional leaders, religious leaders, youth organizations, and representatives from the community. e. Emergency Disaster Management Sector, In the case of natural disasters such as flooding, village heads and village officials are quick to respond and respond to help people whose houses are flooded and damaged. 2. Summative Evaluation, namely: a. The construction of concrete rebate roads had an impact before the construction was carried out where two-wheeled vehicles were difficult to pass during the rainy season. b. The impact of the construction of concrete rebate roads makes it easier to transport agricultural products, cheaper transportation costs and faster time. c. There is no land compensation by the village government to the community, it is difficult to access roads to bring building materials, and the workforce is quite high. d. The decision of the village head to carry out the construction of the concrete rebate road is in accordance with the results of consultations with the community represented by village officials and community leaders.